2008
DOI: 10.1007/s10549-008-0171-6
|View full text |Cite
|
Sign up to set email alerts
|

Expression profile of microRNAs in c-Myc induced mouse mammary tumors

Abstract: c-Myc is a transcription factor overexpression of which induces mammary cancer in transgenic mice. To explore whether certain microRNAs (mirRNA) mediate c-Myc induced mammary carcinogenesis, we studied mir-RNA expression profile in mammary tumors developed from MMTV-c-myc transgenic mice, and found 50 and 59 mirRNAs showing increased and decreased expression, respectively, compared with lactating mammary glands of wild type mice. Twenty-four of these mirRNAs could be grouped into eight clusters because they ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
0
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(68 citation statements)
references
References 64 publications
3
62
0
3
Order By: Relevance
“…Interestingly, weak miR-20b expression can be useful for predicting clinical behavior, enabling a group of MCLs with higher survival probability to be distinguished. MiR-20b expression has been found to have a role in other type of cancers, [61][62][63] in which its high level of expression was associated with a worse prognosis, as is the case for what we found in MCL. It should be noted that miR-20b is localized in a cluster (X chromosome) that shares some similarities with oncomir-1, which is already known to be strongly expressed in MCL cell lines, and is homologous at 21 out of 23 nucleotides with miR-20a, a member of the aforementioned cluster.…”
Section: Discussionsupporting
confidence: 75%
“…Interestingly, weak miR-20b expression can be useful for predicting clinical behavior, enabling a group of MCLs with higher survival probability to be distinguished. MiR-20b expression has been found to have a role in other type of cancers, [61][62][63] in which its high level of expression was associated with a worse prognosis, as is the case for what we found in MCL. It should be noted that miR-20b is localized in a cluster (X chromosome) that shares some similarities with oncomir-1, which is already known to be strongly expressed in MCL cell lines, and is homologous at 21 out of 23 nucleotides with miR-20a, a member of the aforementioned cluster.…”
Section: Discussionsupporting
confidence: 75%
“…MALAT1 is required for the G1-S transition and mitotic progression via the regulation of cell cycle gene expression [196]. Although high MALAT1 expression is associated with poorer outcomes in a number of cancer types [197], it is downregulated in mammary tumors in c-myc transgenic mice [198]. However, the exact role of MALAT1 in breast cancer is still uncertain at this stage, as another line of investigation found that MALAT1 is upregulated in primary breast cancer [199].…”
Section: Nuclear Architectural Rnasmentioning
confidence: 99%
“…[3][4][5] Subsequently, miRNAs have been shown to have important roles in many physiological processes of mammalian systems by influencing cell apoptosis, proliferation, differentiation, development, and metabolism through regulation of critical signaling molecules including cytokines, growth factors, transcription factors, and pro-apoptotic and anti-apoptotic proteins. [6][7][8] Increasing number of miRNAs have been identified in the human genome and they are collectively called the miRNome. 9 Accumulating evidence shows the potential involvement of altered regulation of miRNAs in initiation and progression in a wide range of human cancers.…”
mentioning
confidence: 99%